Hidrólisis enzimática de almidón (2017)
This paper reviews the scientific advances that have been made regarding the understanding of the phenomenon of partial hydrolysis of the starch, using the enzyme Glucoamylase from Aspergillus niger and taking into account that this enzyme; at a structural level has a double (SBD, starch binding domain) binding domain, allowing, on the one hand, its inactivation, and, on the other hand, argues in a starch substrate catalytic activity. The interest of this review, along with the evidence of an empirical model obtained from experimentation and observation after the use of the experimental data in the partial hydrolysis of starch of quinoa, the scope of this review aims to establish major progress made around the establishment of the kinetics of the reaction of enzyme-amylose in starch substrates. However, it is important to clarify that this review does not show what corresponds to the process of enzymatic inactivation and what is related to the enzyme-amylose molecular interaction either.